2021
DOI: 10.1038/s41598-021-88854-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier disruption and ventricular enlargement are the earliest neuropathological changes in rats with repeated sub-concussive impacts over 2 weeks

Abstract: Repeated sub-concussive impact (e.g. soccer ball heading), a significantly lighter form of mild traumatic brain injury, is increasingly suggested to cumulatively alter brain structure and compromise neurobehavioural function in the long-term. However, the underlying mechanisms whereby repeated long-term sub-concussion induces cerebral structural and neurobehavioural changes are currently unknown. Here, we utilised an established rat model to investigate the effects of repeated sub-concussion on size of lateral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Hence, these changes could represent an overall trend toward anti-inflammation, or immune suppression. Interestingly, Hiles-Murison et al, also found suppression of several pro-inflammatory chemokines and cytokines (CXCL1 and MCP-1), although they saw no changes in IL-1β or IL-6 ( 16 ). In a clinical study, Huibregtse et al subjected soccer players to 10 controlled headers and tested plasma levels of pro-inflammatory chemokines (CCL11 and CCL2) and an anti-inflammatory cytokine (IL-10) immediately post-heading, as well as 2 h and 24 h later ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these changes could represent an overall trend toward anti-inflammation, or immune suppression. Interestingly, Hiles-Murison et al, also found suppression of several pro-inflammatory chemokines and cytokines (CXCL1 and MCP-1), although they saw no changes in IL-1β or IL-6 ( 16 ). In a clinical study, Huibregtse et al subjected soccer players to 10 controlled headers and tested plasma levels of pro-inflammatory chemokines (CCL11 and CCL2) and an anti-inflammatory cytokine (IL-10) immediately post-heading, as well as 2 h and 24 h later ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from our group, we reported ventricular enlargement and blood brain barrier (BBB) disruption after 60 subconcussive impacts over 2 weeks with no disruption to neuronal function ( 13 ). Parenchymal perivascular extravasation of plasma IgG was quantified to assess integrity of BBB integrity in the cortex and the hippocampal formation in these rats which exhibited significantly exaggerated cortical perivascular IgG extravasation and significant leakage of parenchymal IgG in the hippocampal region compared with the rats in the sham group ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from our group, we reported ventricular enlargement and blood brain barrier (BBB) disruption after 60 subconcussive impacts over 2 weeks with no disruption to neuronal function ( 13 ). Parenchymal perivascular extravasation of plasma IgG was quantified to assess integrity of BBB integrity in the cortex and the hippocampal formation in these rats which exhibited significantly exaggerated cortical perivascular IgG extravasation and significant leakage of parenchymal IgG in the hippocampal region compared with the rats in the sham group ( 13 ). Furthermore, the “silent” cerebro-structural and -vascular alterations were observed not only at the impact site (cortex), but also in the deeper regions of the brain; the hippocampus and lateral ventricle, indicating a potentially distinct neuropathological pathway from those ordinarily observed in concussion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that for the lone study which used an easier variant of the 5CSRT task, this was limited to omissions ( Kaukas et al, 2021 ). Additional studies have indicated that “subconcussive” impacts may also generate pathology and ultimately functional impairment if repeated frequently enough ( Lavender et al, 2020 ; Hiles-Murison et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%